Dynamic Query Plan for Efficient Query Processing in Peer-to-Peer Environments - Masud, Mehedi; Hossain, M. A. (INFOCOMP Journal of Computer Science, 2008)
In the past few years, Peer-to-Peer (P2P) applications have emerged as a popular way of autonomously sharing data and services in distributed environments. In such environments, peers dynamically join/leave a network and do not usually have any global knowledge about the data sources. This phenomenon demands an efficient query execution strategy in terms of data transmission and response time. In this paper, we propose a distributed query processing technique in P2P environments where each peer possesses partial knowledge of the domain information and collaborates with the participating peers to share data. The cornerstone of our approach is to dynamically determine the best query execution plan in order to execute the different parts of the user query, and propagate the results with minimized data transmission and response time.